Recovery of 3D objects from 2D drawings Part I - Ang, Ian Yu Zheng (2011)
This report presents a simple method, referred to as “Backward Process”, of recovering 3D objects from a single 2D perspective drawing. The ability to do so has numerous applications and is particularly valuable in the field of artificial intelligence. This report focuses on 2-point perspective images and first studies a common method, referred to as “Forward Process”, which is used in producing perspective drawings of known 3D objects. This method starts with two orthographic projections of the object – plan view and side elevation. Certain constraints such as the geometry of the object, orientation of the object and the location of the Station Point of the object are necessary in the use of this method; along with arbitrary parameters such as the location of the horizon and vanishing points. The “Forward Process” is then reversed to produce the said “Backward Process”. The “Backward Process” starts with a single perspective drawing of a 3D object which meets the constraints set out in the “Forward Process” and retrieves crucial information such as the horizon, vanishing points and Station Point from it.